Comparative effectiveness of amoxicillin versus amoxicillin‐clavulanate among adults with acute sinusitis in emergency department and urgent care settings - Suzette A. Rovelsky; Richard E. Remington; McKenna Nevers; Benjamin Pontefract; Adam L. Hersh; Matthew Samore; Karl Madaras‐Kelly (Journal of the American College of Emergency Physicians Open)
Abstract Objective To compare the effectiveness of amoxicillin‐clavulanate versus amoxicillin for adults diagnosed with acute sinusitis (AS). A secondary objective compared antibiotic effectiveness in patients meeting risk criteria for treatment failure. Methods A retrospective cohort study of adults diagnosed with AS prescribed amoxicillin ± clavulanate within Veterans Affairs emergency departments from 2012–2019 was conducted. The primary outcome was sinusitis‐related return visits for amoxicillin versus amoxicillin‐clavulanate. Secondary outcomes included 30‐day infectious complications, gastrointestinal‐related adverse events (AEs), and hospitalizations. Propensity‐score matching and logistic regression models adjusted for potential confounders. Results A total of 89,627 AS patient visits were identified: 18,576 prescribed amoxicillin and 71,051 amoxicillin‐clavulanate. Most patients were male (75,604; 84.4%) and afebrile (80,624; 91.7%). The propensity score‐matched cohort comprised 17,929 amoxicillin and 42,294 amoxicillin‐clavulanate patient visits. There was no difference in sinusitis‐related return visits between amoxicillin (4.9%) and amoxicillin‐clavulanate (5.1%) (adjusted odds ratio [OR], 0.96; 95% confidence interval [CI], 0.88, 1.04; P = 0.317). Infectious complications (amoxicillin [0.3%] vs amoxicillin‐clavulanate [0.4%]); (adjusted OR, 0.78; 95% CI, 0.57, 1.07; P = 0.124) and hospitalization (amoxicillin [2.0%] vs amoxicillin‐clavulanate [2.4%]); (adjusted OR, 0.92; 95% CI, 0.81, 1.04; P = 0.173) were not different. Gastrointestinal‐related AEs were lower with amoxicillin (0.5%) relative to amoxicillin‐clavulanate (0.7%); (adjusted OR, 0.67; 95% CI, 0.53, 0.86; P = 0.002). Comorbidity was the only guideline‐recommended risk factor that was a significant predictor of infectious complications with respect to treatment (amoxicillin vs amoxicillin‐clavulanate, OR, 0.63; 95% CI, 0.40 to 0.94; P = 0.022). Conclusion Amoxicillin demonstrated similar efficacy to amoxicillin‐clavulanate for AS with fewer gastrointestinal‐related AEs. Amoxicillin is a viable option in adults with AS meeting criteria for antibiotic therapy.